Implikasi Ambiguitas Kreditur Separatis Dan Kurator Dalam Pembagian Boedel Debitor Pailit Menurut Perspektif Philosophy - Saija, Ronald; Tesalonika, Iming Maknaan; Bakir, Herman (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2024)
Introduction: Completing debt and receivables agreements with serious material security objects between creditors and debtors through the Bankruptcy route. Bankruptcy as a form of dispute resolution regulated in Articles 749-910 of Wetboek van Koophandel which has been codified through Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Purposes of the Research: To find legal rules that specifically regulate the Ambiguity Implications of Separatist Creditors and Curators in Boedel, Debtors Bankruptcy. Methods of the Research: The method used in this writing is an extensive interpetation method to try to find a law in the future (ius constituendum) because there is still no legal rule that specifically regulates the Ambiguity Implications of Separatist Creditors and Curators in Boedel Debtors Bankruptcy. Then we also use a systematic interpretation method because in this study the author tries to relate several laws and regulations in Indonesia. Results Originality of the Research: The bankruptcy study is inseparable from the collateral by the debtor who has experienced business bankruptcy, which has given an advantage to separatist creditors and curators in executing the collateral before it is further studied by the Government through the Curator. In fact, through its superior nature, the settlement of receivables by separatist creditors is quite ambigiutive and comprehensive and fast without having to apply for bankruptcy of the previous debtor.